2020
DOI: 10.1002/jimd.12224
|View full text |Cite
|
Sign up to set email alerts
|

Dietary lipids in glycogen storage disease type III: A systematic literature study, case studies, and future recommendations

Abstract: Summary A potential role of dietary lipids in the management of hepatic glycogen storage diseases (GSDs) has been proposed, but no consensus on management guidelines exists. The aim of this study was to describe current experiences with dietary lipid manipulations in hepatic GSD patients. An international study was set up to identify published and unpublished cases describing hepatic GSD patients with a dietary lipid manipulation. A literature search was performed according to the Cochrane Collabora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
32
2
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(40 citation statements)
references
References 34 publications
(88 reference statements)
3
32
2
3
Order By: Relevance
“…At that time she was introduced a high carbohydrates diet (frequent diurnal and nocturnal cornstarch meals); carbohydrates (9 g/kg per day (g/kg/d)) contributed 53% daily calories, proteins (4 g/kg/d) contributed 23% and fats (1.8 g/kg/d) contributed another 23%, according to the recommendations [2] . Progressively she developed left ventricular obstructive hypertrophy, hepatomegaly and skeletal myopathy with highly elevated liver and muscle enzymes, as previously reported [3] , [4] , [5] , [6] . She also presented recurrent hypoglycemic events despite treatment with frequent diurnal and nocturnal meals with cornstarch supplements.…”
Section: Experimental Design Materials and Methodssupporting
confidence: 75%
“…At that time she was introduced a high carbohydrates diet (frequent diurnal and nocturnal cornstarch meals); carbohydrates (9 g/kg per day (g/kg/d)) contributed 53% daily calories, proteins (4 g/kg/d) contributed 23% and fats (1.8 g/kg/d) contributed another 23%, according to the recommendations [2] . Progressively she developed left ventricular obstructive hypertrophy, hepatomegaly and skeletal myopathy with highly elevated liver and muscle enzymes, as previously reported [3] , [4] , [5] , [6] . She also presented recurrent hypoglycemic events despite treatment with frequent diurnal and nocturnal meals with cornstarch supplements.…”
Section: Experimental Design Materials and Methodssupporting
confidence: 75%
“…Rossi et al [5] and many other authors have shown the cardiac pathology of GSD IIIa to benefit from high-fat diet [5,18,19]. The median duration of diet in the study of of Rossi et al [5] was 18 months, which is longer than that in the present report. In our study group, 2 patients with hypertrophic cardiomyopathy had carried on MAD for a relatively short period of time (5-7 months), and no apparent differences between cardiac parameters were observed.…”
Section: Discussioncontrasting
confidence: 52%
“…In both patients, CK levels in blood decreased, cardiomyopathy improved and associated symptoms disappeared [ 6 ]. Furthermore, a recent cohort study by Rossi et al reveals a decrease of CK levels in 89% of patients with GSD type IIIa treated with high fat diet [ 7 ]. Francini-Pesenti et al report on a 34 years-old patient with GSD type IIIa with hypertrophic cardiomyopathy who was also treated with a MAD.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding hepatopathy, Rossi et al also report a decrease of ALT and AST concentrations in adults in 100% and 83% patients, respectively. In children, ALT and AST decrease in only 11% and 22% patients, respectively [ 7 ]. An improvement of ALT and AST levels is reported by Brambilla (AST of 21% and 72%; ALT of 6 and 38%) and Francini-Pesenti (AST of 29% and ALT of 24%), but they do not report any change in liver sizes [ 6 , 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation